Improving Sociology Learning Outcomes in Class X IPS 1 Students Through Models Contextual Teaching Learning at SMA Negeri 12 West Seram District, West Seram Regency - Maryam Putri Rumagiar; R. Tutupary; Lambertus J. Lokollo (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study is to describe the learning outcomes of sociology in Class X Social1 students through the Sciences Contextual Teching Learning model at SMA Negeri 12 West Seram District, West Seram Regency. The type of research used is classroom action research (Classroom Action Research). This study refers to the Spiral Model of Kemmis and Tagrat. The results showed that in the first cycle the students had not achieved many of the criteria for completeness and in the second cycle they had achieved the KKM results very well. And thus do not continue in the next cycle